tRNA-derived small RNAs (tsRNAs): establishing their dominance in the regulation of human cancer - Li Gong; Yajie Hu; Ling Pan; Ling Pan; Yufeng Cheng; Yufeng Cheng (Frontiers in Genetics)
The main function of transfer RNAs (tRNAs) is to carry amino acids into the ribosome and synthesize proteins under the guidance of messenger RNAs (mRNAs). In addition to this, it has been observed that tRNAs undergo precise cleavage at specific loci, giving rise to an extensive array of distinct small RNAs, termed tRNA-derived small RNAs (tsRNAs). Existing studies have shown that tsRNAs are widely present across various organisms and comprehensively regulate gene expression, aberrant expression of tsRNAs is inextricably linked to tumorigenesis and development, thus, a systematic understanding of tsRNAs is necessary. This review aims to comprehensively delineate the genesis and expression patterns of tsRNAs, elucidate their diverse functions and emphasize their prospective clinical application as biomarkers and targets for therapy. It is noteworthy that we innovatively address the roles played by tsRNAs in human cancers at the level of the hallmarks of tumorigenesis proposed by Hanahan in anticipation of a broad understanding of tsRNAs and to guide the treatment of tumors.